2021
DOI: 10.1021/acsami.0c21010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights for Photoelectrochemical Ethanol Oxidation on Black Gold Decorated Monoclinic Zirconia

Abstract: Surface decoration of metal oxides by metals for enhancing their electrocatalytic properties for organic conversions has attracted a lot of researchers’ interest due to their high abundancy, inexpensiveness, and high stability. In the present work, a process for the synthesis of black gold (BG) using a citrate assisted chemical route and m-ZrO2 by a hydrothermal method at 200 °C has been developed. Further, different concentrations of black gold are being used to decorate the surface of zirconia by exploitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 68 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…49 A peak potential was observed corresponding to the oxidation peak due to NVO loading in the nanocomposites. 48,50 This also shows that with an increase in the NVO concentration in composites, photocurrent density increases up to that of NVO-1@g-CN. Further loading results in diminishing photocurrent density.…”
Section: Resultsmentioning
confidence: 70%
“…49 A peak potential was observed corresponding to the oxidation peak due to NVO loading in the nanocomposites. 48,50 This also shows that with an increase in the NVO concentration in composites, photocurrent density increases up to that of NVO-1@g-CN. Further loading results in diminishing photocurrent density.…”
Section: Resultsmentioning
confidence: 70%
“…It has been reported that small Au nanoparticles assemble to form black Au structures. [ 28–31 ] Highly branched superparticles are synthesized through the morphological modulation in the seeded growth process. [ 32 ] Porous or fibrous templates are used to deposit Au or Au nanoparticles through evaporation or wet chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of biomass alcohols and their derivatives, e.g. ethanol 8 10 , glycerol 11 13 , glucose 14 16 , methanol 17 , 18 , and benzyl alcohol 3 , 6 , 7 , 19 , has been previously investigated to replace OER and promote hydrogen production via a photoelectrochemical process using various semiconductor electrode systems. However, the development of facile routes for transformation of alcohols remains a big challenge due to low conversion and selectivity, limited charge transport and reaction kinetics, and limited efficiency because of reactor design issues.…”
Section: Introductionmentioning
confidence: 99%